2020
DOI: 10.1097/md.0000000000022524
|View full text |Cite
|
Sign up to set email alerts
|

The effect of adding intrathecal magnesium sulphate to bupivacaine-fentanyl spinal anesthesia

Abstract: Trial design: The current study is a meta-analysis designed to assess the effect of adding magnesium to a combination of intrathecal bupivacaine and fentanyl. Methods: The protocol was registered in PROSPERO with the number CRD42020177618. PubMed, Cochrane library, Web of Science, and Google Scholar were searched for randomized controlled trials investigating the effect of adding magnesium to a combination of intrathecal bupivacaine and fentanyl. The continuous data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Magnesium acts as an antagonist for NMDA receptors and can relieve pain. The pain relief effect of magnesium has been confirmed in intra- and postoperative periods ( 19 - 21 ).…”
Section: Introductionmentioning
confidence: 85%
“…Magnesium acts as an antagonist for NMDA receptors and can relieve pain. The pain relief effect of magnesium has been confirmed in intra- and postoperative periods ( 19 - 21 ).…”
Section: Introductionmentioning
confidence: 85%
“…Sixteen included studies were systematic reviews and meta-analyses of RCTs, while one study was a systematic review of RCTs [21]. Routes of magnesium administration were intravenous in seven studies [21][22][23][24][25][26][27], intrathecal and/or epidural in five [16,17,[28][29][30], and intra-articular in two [31,32]. There were several routes, including intravenous, intrathecal, epidural, and local approaches, in three studies [17,18,20].…”
Section: Description Of Included Systematic Reviewsmentioning
confidence: 99%
“…Summarized evidence on analgesic consumption is shown in Table 3. Nine studies performed meta-analyses to assess the time interval to the first analgesic request following surgery [17,22,24,[27][28][29][30][31][32]. Time to first analgesic request was significantly shorter in the majority of studies although heterogeneity was substantial; the details are presented in Table 4.…”
Section: Summary Of the Evidencesmentioning
confidence: 99%
“…It is an NMDA antagonist that reduces central sensitization. These receptors are activated by surgical stimulus (7). Studies demonstrated no signi cant side effects in intrathecal magnesium sulfate injection (8, 9).…”
Section: Introductionmentioning
confidence: 99%